Ultrasound‐assisted extraction of oil from hempseed (Cannabis sativa L.): Part 2. (22nd September 2022) - Girotto, Francesca; Esposito, Marilena; Piazza, Laura
Abstract: BACKGROUND: Oilseed‐matrix consolidation is a crucial factor when talking about oil expression because, as the cake consolidates, the coefficient of permeability inevitably decreases. Thus, any treatment that extensively ruptures cell walls reduces rigidity and hardness of the oilseed press‐cake, while improving the oil expression. Such process intensification was investigated in the present study through the introduction of the ultrasound (US) technology. Screw pressing of Cannabis sativa L. seeds was operated using a pilot scale equipment set at three different pressures (low, medium and high) to understand the correlation with the ultrasound effectiveness. Samples of non‐exhausted press‐cakes were tested for objective instrumental indices of compressibility and oil expression yields prior and after the US treatment. RESULTS: US led to a drag resistance reduction within press‐cakes, improving oil flowability through a decrease in the material cohesiveness and adhesiveness. Consistently, sonication favoured oil extraction yields and oil antioxidant capacities, which increased with respect to the untreated samples, respectively equal to +19.2% and + 29.4% for the press‐cake screwed at low pressure, to +21.8% and + 49.3% at medium pressure, and to +15.4% and + 0.5% at high pressure. Overall, US highest effectiveness was accounted for samples screwed at medium pressure. CONCLUSION: Press‐cake compressibility can be well described by macroscopic texture parameters; indeed, their decrease is linked to higher oil expression efficiencies. Sonication can help boosting oil extraction yields reducing drag resistance within the mechanical screwing equipment. These outcomes offer good potentials for US application in the hempseed technology and, more extensively, in the oil seed industry. © 2022 Society of Chemical Industry.